Reactivating Local Wisdom Values and Religious Rituals as A Means to Achieve Social Harmony Among Religius Communities - Husna, Aviyah Asmaul; Hamid, Abdur Rahman Nor Afif (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
This study explores the reactivation of local wisdom and religious practices within the framework of social harmony and religious identity reinforcement. The aim of this study is to assess the contributions of local wisdom and religious rituals in fostering social harmony among various religious groups and in strengthening religious identity in the contemporary era. The research employs a qualitative approach using library research. The findings indicate that the reactivation of local wisdom and religious rituals can substantially serve as a foundation for creating social harmony and reinforcing religious identity. Local wisdom acts as a bridge between religious communities through values of tolerance, solidarity, and togetherness, while religious rituals enhance social cohesion and understanding between religious groups. The discussion in this article highlights that local wisdom and religious practices can be adapted to modernization without losing their traditional essence, thus supporting inclusive social integration. In conclusion, the reactivation of local wisdom and religious rituals, when integrated with contemporary values, can strengthen social harmony and religious identity in a pluralistic society.